Deproteinized bovine bone mineral particles and osseointegration of implants without primary bone contact: An experimental study in dogs - Sivolella, Stefano; Bressan, Eriberto; Salata, Luiz A.; Quiñones, Maria E.; Lang, Niklaus P.; Botticelli, Daniele (Wiley, 2013)
Objectives: To evaluate the influence on osseointegration of Deproteinized bovine bone mineral (DBBM) particles used to fill defects of at least 1 mm around implants having no primary contact with bone. Material and methods: Premolars and first molars were extracted bilaterally from the mandible of six Labrador dogs. After 3 months of healing, mucoperiosteal full-thickness flaps were elevated, and one recipient site was prepared in the molar region of each hemi-mandible to place implants. These were installed with a deliberate circumferential and periapical space to the bone walls of 1.2 mm. All implants were stabilized with passive fixation plates to maintain the implants in situ and without any contact with the implant bed. The control sites were left to be filled with coagulum, while at the test sites, the residual gap was filled with DBBM. After 3 months of submerged healing, the animals were sacrificed. Ground sections were prepared and analyzed histomorphometrically. Results: Mineralized bone-to-implant contact was 4.0% and 3.9% for control and test sites, respectively. The width of the residual defects was 0.48 mm and 0.88 mm at the control and test sites, respectively. The percentage of implant surface covered by a layer of dense connective tissue of 0.12 mm of width on average was 84.9% and 88.5% at the control and test sites, respectively. Conclusion: A minor and not predictable degree of contact or distance osteogenesis was obtained on the implant surface when primary contact of the implant surface with the implant bed had deliberately been avoided. DBBM grafting of the artificial gap did not favor osseointegration. Neither did it enhance the ability to bridge the gap with newly formed bone in an artificial defect wider than 1 mm. © 2013 John Wiley & Sons A/S.
Keywords: Animal study; Bone contact; Bone healing; Contact osteogenesis; Defect; Deproteinized bovine bone mineral; Distance osteogenesis; Implant dentistry; Osseointegration